The Positive Pharmacy Care Law revisited: an area-level analysis of the relationship between community pharmacy distribution, urbanicity and deprivation in England - Clare Bambra; Adam Todd; Luke Aaron Munford; Adetayo Kasim; Alison Copeland; Andy Husband; Eman Zied Abozied (BMJ Open)
Objectives (1) Determine geographical access to community pharmacy in England, (2) explore the relationship between community pharmacy access and urbanity and multiple deprivation and (3) understand any changes in access over time.Design An area-level spatial analysis study exploring the relationship between spatial access to and availability of community pharmacies over the past 10 years from 2014 to 2023, deprivation and urbanicity, using Geographic Information System and descriptive statistics on a Middle layer Super Output Area level.Primary outcome measure Availability per 10 000 people of a community pharmacy in their local area.Results For geographical access, in 2014, 91.3% of people lived within a 20-minute walk to a community pharmacy and, in 2023, this number increased to 91.7%. There was a positive relationship between geographical community pharmacy access and urbanity and geographical community pharmacy access and deprivation. For availability, the median number of community pharmacies per 10 000 people in 2014 was 1.60, while in 2023, the number reduced to 1.51 community pharmacies per 10 000 people. The most deprived areas were more likely to lose a pharmacy, compared with the least deprived areas (OR 1.65 (1.38, 1.98)).Conclusions There is high access to community pharmacies in England with access to a community pharmacy greatest in the most deprived areas, showing that the ‘positive pharmacy care law’ remains. However, the ‘positive pharmacy care law’ is eroding as the availability of community pharmacies has reduced over time—particularly in deprived areas, with more people reliant on each community pharmacy.